Recurrent pulmonary embolism associated with deep venous thrombosis diagnosed as protein s deficiency owing to a novel mutation in PROS1: A case report. Issue 19 (May 2018) - Huang, Xiaojie; Xu, Fangfang; Assa, Carmel Rebecca; Shen, Laigen; Chen, Bing; Liu, Zhenjie
Abstract: Rationale: Protein S (PS) deficiency that can be inherited or acquired is an independent risk factor for venous thromboembolism (VTE). Patient concerns: In this report, we present a case of recurrent pulmonary embolism (PE) and deep venous thrombosis (DVT) due to PS deficiency. Diagnoses: A 32-year-old male patient with significant decrease in PS activity was detected by laboratory tests. Genetic examination of the PROS1 gene showed a transition of G to T in exon 14 (c.1792 G>T, p.E598X), which was a paternal inherited heterozygous G1792T substitution in the laminin G-type repeat domain, generating a premature stop codon at Glu598. Interventions: We considered that the inherited PS deficiency due to a PROS1 gene mutation may associate with recurrent VTE. The patient was suggested to have an extended anticoagulant therapy to avoid a severe VTE event. Outcomes: The patient was discharged home with continued oral anticoagulants and was still seen in clinic for follow-up. Lessons: It is necessary for the young patient with recurrent idiopathic thrombosis to perform an inherited PS deficiency test and receive anticoagulant therapy for an extended period.